Assessment of Seismic Capacity for Reinforced Concrete Frames with Perforated Unreinforced Brick Masonry Infill Wall - Muhammad Umar; Syed Azmat Ali Shah; Khan Shahzada; Muhammad Tayyab Naqash; Wajid Ali (Salehan Institute of Higher Education, 2020)
Infill walls increase the strength and stiffness of the reinforced concrete frames, but they usually are not considering in design. However, when the infills are considered in the design, the opening for doors/windows necessitates investigation as well. This research work aims to investigate the effect of perforations (openings) in the infill walls on the performance of infilled RC frames, in other words, this research investigates the number of infill walls in infilled RC frames. Based on the current construction practices in Pakistan, two full scales perforated infilled RC frames were constructed in the laboratory. One infilled RC frame has an eccentric door and window (specimen-1) while the other has only window at its centre (specimen-2). Both the specimens were tested against reverse cyclic loading (quasi-static test). From the experimental testing, it was found that infilled RC frame having less amount of opening in infill wall has more resistance to lateral loads, have more stiffness and dissipated higher energy as compared to infilled RC frame having a significant size of the opening in infill wall. Similarly, displacement ductility (µD) and Response modification factor (R) also depend on the quantity of opening in infill wall in infilled RC frame. Doi: 10.28991/cej-2020-03091625 Full Text: PDF